Work Safety in A Selected Carpentry Workshop - Michał PAŁĘGA; Bartosz FOGIEL (Communications of International Proceedings, 2023)
Ensuring safe and hygienic working conditions is the basic duty of every employer. The implementation of this obligation requires a systematic examination of all aspects of work, which is carried out in order to determine what hazards in the working environment may cause injury or deterioration of the employee's health and whether these hazards can be eliminated, and if not - what actions should be taken to reduce occupational risks associated with these hazards. A properly conducted occupational risk assessment should prevent the harmful effects of hazards in the work environment. In view of the above, it is important to have access to reliable scientific information in the field of practical risk assessment at selected workplaces. The article presents the characteristics of a carpenter's workplace and assesses the occupational risk for the discussed position in a selected industrial enterprise. As part of the conducted research, occupational hazards were identified (based on the analysis of documentation and passive observation of the workplace), and the hazards were assessed using the Risc Score method. Then, the directions of actions aimed at increasing the level of safety of employees employed as a carpenter in a selected production plant were proposed. This article is a supplement to the knowledge in the field of identification and assessment of occupational hazards occurring at the tested workplace.
Keywords: health and safety; working environment; threats; risk assessment; carpenter